2022
DOI: 10.3390/ijerph192114063
|View full text |Cite
|
Sign up to set email alerts
|

Serious Injury in Metropolitan and Regional Victoria: Exploring Travel to Treatment and Utilisation of Post-Discharge Health Services by Injury Type

Abstract: This study aimed to describe regional variations in service use and distance travelled to post-discharge health services in the first three years following hospital discharge for people with transport-related orthopaedic, brain, and spinal cord injuries. Using linked data from the Victorian State Trauma Registry (VSTR) and Transport Accident Commission (TAC), we identified 1597 people who had sustained transport-related orthopaedic, brain, or spinal cord injuries between 2006 and 2016 that met the study inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…Medicare and Medicaid patients of all race categories had poorer outcomes than privately insured White patients [81]. People with TBI living in more rural areas traveled significantly further to access postdischarge health services and had decreased amounts of follow-up healthcare appointments [58]. Countries with a high incidence of TBI has disproportionately higher research publications compared to countries with lower TBI populations [65].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medicare and Medicaid patients of all race categories had poorer outcomes than privately insured White patients [81]. People with TBI living in more rural areas traveled significantly further to access postdischarge health services and had decreased amounts of follow-up healthcare appointments [58]. Countries with a high incidence of TBI has disproportionately higher research publications compared to countries with lower TBI populations [65].…”
Section: Discussionmentioning
confidence: 99%
“…The citations for the studies included in this analysis can be found in the Reference section [34,36,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68].…”
Section: Data Extraction and Synthesismentioning
confidence: 99%
“…A major obstacle to participation for people with disabilities is their common perception of travel failures as being inevitable [15]. While studies have analyzed the inaccessible service and environmental barriers affecting the travel decisions of people with disability [16,17], constraint theory further suggests that unless their psychological inhibitors (i.e., hesitation or fear of failures) are resolved [18], they will not be in the position to experience objective environmental inhibitors (i.e., architectural barriers or lack of adapted transportation). In such cases, improving the objective physical travel settings will not necessarily trigger their travel motivation [19].…”
Section: Travel and Tourism Participation Of Pwscimentioning
confidence: 99%